An Interpretation of The Beatles’ Music - Vas, József Pál (Research Developments in Arts and Social Studies Vol. 4, 2022)
The purpose of this paper is to define the components of the Beatles' impact on popular culture during the 1960s. Their new musical style has such characteristics that it can appeal to individuals all around the world. While listening to their music, these characteristics will be examined. The first inquiry is about their song's origins. They clearly have roots in both Western and Eastern folk music, not just rhythm and blues. The second topic concerns whether or not standard tone functions alter the emotional impression. The answer is that the Minor tonality has got such function as the Major does: joy, brightness, and happiness. The third feature is their striving after synthesis between classical and pop music. The fourth feature can be seen as a synthesis between eras and cultures, i.e. modern and Baroque. Finally, I mention to hold such music groups for psychiatric patients when listened to music of The Beatles.